LncRNA-DANCR Interferes With miR-125b-5p/HK2 Axis to Desensitize Colon Cancer Cells to Cisplatin vis Activating Anaerobic Glycolysis - Shi, Huijuan; Li, Kejun; Feng, Jinxin; Liu, Gaojie; Feng, Yanlin; Zhang, Xiangliang (Frontiers in Oncology, 2020)
Colon cancer is one of the most prevalent malignancies which lead to high occurrence of cancer-related deaths. Currently, chemo- and radio- therapies remain the primary treatment for advanced colon cancer. Despite the initial effectiveness, a fraction of colon cancer patients develops cisplatin resistance, resulting in therapeutic failure. The long non-coding RNA DANCR has been shown to be upregulated in multiple cancers, indicating an oncogenic role of DANCR. This study aims to elucidate the roles of DANCR in regulating cisplatin (CDDP) resistance of colon cancer. We found DANCR was significantly upregulated in colon cancer tissues and cells compared with normal colon tissues and cells. DANCR was upregulated in cisplatin resistant colon cancer cells. Moreover, overexpression of DANCR significantly de-sensitized colon cancer cells to cisplatin. On the other way, silencing DANCR dramatically overrode CDDP resistance of colon cancer cells. Bioinformatics prediction revealed DANCR could bind to seeding region of miR-125b-5p as a competitive endogenous RNA (ceRNA). This interference was further validated by luciferase assay. Moreover, we detected a negative correlation between DANCR and miR-125b-5p in colon cancer patient tissues: miR-125b was clearly downregulated in colon cancer tissues and cells. Overexpression of miR-125b significantly sensitized cisplatin resistant cells. Interestingly, we observed the cisplatin resistant cells were associated with a significantly increased glycolysis rate. We further identified glycolysis enzyme, Hexokinase 2 (HK2) as a direct target of miR-125b-5p in colon cancer cells. Rescue experiments showed overexpression of miR-125b suppressed cellular glycolysis rate and increased cisplatin sensitivity through direct targeting the 3’UTR of HK2. Importantly, silencing endogenous DANCR significantly induced the miR-125b/HK2 axis, resulting in suppression of the glycolysis rate and increasement of cisplatin sensitivity of colon cancer cell. Expectedly, these processes could be further rescued by inhibiting miR-125b in the DANCR-silenced cells. Finally, we demonstrated the DANCR-promoted cisplatin resistance via the miR-125b/HK2 axis from an in vivo xenograft mice model. In summary, our study reveals a new mechanism of the DANCR-promoted cisplatin resistance, presenting lncRNA-DANCR-miR-125b/HK2 axis as a potential target for treating chemoresistant colon cancer.